Searching for a tactile target: the impact of set-size on the N140cc - Gherri, Elena; Fiorino, Fabiola Rosaria; Iani, Cristina; Rubichi, Sandro (Frontiers in Human Neuroscience, 2023)
The time needed to find a visual target amongst distractors (search task) can increase as a function of the distractors’ number (set-size) in the search-array (inefficient search). While the allocation of attention in search tasks has been extensively investigated and debated in the visual domain, little is known about these mechanisms in touch. Initial behavioural evidence shows inefficient search behaviour when participants have to distinguish between target and distractors defined by their vibro-tactile frequencies. In the present study, to investigate the allocation of attention to items of the search-array we measured the N140cc during a tactile task in which the set-size was manipulated. The N140cc is a lateralized component of event-related brain potentials recently described as a psychophysiological marker of attentional allocation in tactile search tasks. Participants localized the target, a singleton frequency, while ignoring one, three or five homogeneous distractors. Results showed that error rates linearly increased as a function of set-size, while response times were not affected. Reliable N140cc components were observed for all set-sizes. Crucially, the N140cc amplitude decreased as the number of distractors increased. We argue that the presence of additional distractors hindered the preattentive analysis of the search array resulting in increased uncertainty about the target location (inefficient preattentive stage). This, in turn, increased the variability of the deployment of attention to the target, resulting in reduced N140cc amplitudes. Consistent with existing behavioural evidence, these findings highlight systematic differences between the visual and the tactile attentional systems.